Contemporary achievement capabilities bronchial endoscopy - Świerkocki, Krzysztof (Przewodnik Lekarza/Guide for GPs Supplement, 2007)
This paper presents a brief account of the evolution, indications, contradictions and bronchofibroscopy methods of examinations of the respiratory system. It covers modern methods of diagnosis and therapy of respiratory system diseases using fibroscopy. Examples of the examinations are presented.